Myocardial proteome changes in aortic stenosis rats subjected to long-term aerobic exercise - Mota, Gustavo Augusto Ferreira [UNESP]; de Souza, Sérgio Luiz Borges [UNESP]; Vileigas, Danielle Fernandes; da Silva, Vitor Loureiro [UNESP]; Sant'Ana, Paula Grippa [UNESP]; Costa, Licia Carla da Silva; Padovani, Carlos Roberto [UNESP]; Zanatti Bazan, Silméia Garcia [UNESP]; Buzalaf, Marília Afonso Rabelo; Santos, Lucilene Delazari dos [UNESP]; Okoshi, Marina Politi [UNESP]; Gatto, Mariana [UNESP]; et al. (Wiley, 2024)
The effects of exercise training (ET) on the heart of aortic stenosis (AS) rats are controversial and the mechanisms involved in alterations induced by ET have been poorly clarified. In this study, we analyzed the myocardial proteome to identify proteins modulated by moderate-intensity aerobic ET in rats with chronic supravalvular AS. Wistar rats were divided into four groups: sedentary control (C-Sed), exercised control (C-Ex), sedentary aortic stenosis (AS-Sed), and exercised AS (AS-Ex). ET consisted of five treadmill running sessions per week for 16 weeks. Statistical analysis was performed by ANOVA or Kruskal–Wallis and Goodman tests. Results were discussed at a significance level of 5%. At the end of the experiment, AS-Ex rats had higher functional capacity, lower blood lactate concentration, and better cardiac structural and left ventricular (LV) functional parameters than the AS-Sed. Myocardial proteome analysis showed that AS-Sed had higher relative protein abundance related to the glycolytic pathway, oxidative stress, and inflammation, and lower relative protein abundance related to beta-oxidation than C-Sed. AS-Ex had higher abundance of one protein related to mitochondrial biogenesis and lower relative protein abundance associated with oxidative stress and inflammation than AS-Sed. Proteomic data were validated for proteins related to lipid and glycolytic metabolism. Chronic pressure overload changes the abundance of myocardial proteins that are mainly involved in lipid and glycolytic energy metabolism in rats. Moderate-intensity aerobic training attenuates changes in proteins related to oxidative stress and inflammation and increases the COX4I1 protein, related to mitochondrial biogenesis. Protein changes are combined with improved functional capacity, cardiac remodeling, and LV function in AS rats.
Keywords: aerobic exercise training; myocardium; proteomics; rat; supravalvular aortic stenosis; ventricular dysfunction